Surgical and clinical management of neutropenic enterocolitis seen in hematological and solid organ malignancies - Sezgin Uludag, Server; Tunc, Emre; Necati Sanli, Ahmet; Elverdi, Tugrul; Velidedeoglu, Mehmet; Simsek, Osman; Pekmezci, Salih; Kagan Zengin, Abdullah (Annals of Medical Research, 2021)
Aim: Ileocecal syndrome also called typhilite; It is defined as inflammation of the cecum and surrounding tissues seen in immunosuppressed patients. Typhilite is a serious disease in the ileum, cecum, and ascending colon with segmental inflammation and necrosis due to ulceration. The disease has difficulties in its diagnosis, treatment, and surgery. We aimed to examine the difficulties in diagnosis and treatment in this disease, which has high morbidity and mortality.Materials and Methods: Patients who have hematological or solid organ malignancies, diagnosed with neutropenic enterocolitis between January 2014 and December 2019 were included in the study. The demographic information, malignancies, chemotherapy treatments, follow-ups, clinical symptoms, laboratory, and radiology findings of the patients were examined.Results: A total of 7 patients were identified between the dates indicated, 4 were male and 3 were female. The mean age was 58.5. Six of these patients had hematological and one had solid organ malignancy. All patients had the typical fever (above 38), non-migratory abdominal pain localized to the right lower quadrant, and neutropenia (0.5 x10³/mm³). The mean value of Neutrophil at the time symptoms began was 0.15x10³/mm³. Intestinal wall thickening, mesenteric inflammation findings were present in all patients, and pneumocystis intestinalis and perforation were detected in one patient. As presented patients, with increased experience, most of the patients were demonstrated to be treated with consisting of aggressive fluid resuscitation, correction of electrolyte imbalance, bowel rest, and wide-spectrum antibiotics. Two patients died due to severe fungal infection.Conclusion: It is hard to make a common algorithm for diagnosis for NE because NE is a pre-diagnosis. Due to its clinical heterogeneity, treatment modality ranges from surgical treatment to conservative approach. As a result of higher success rates of conservative management, supportive care, and close follow up have replaced surgery in the treatment of this disease.
Keywords: Chemotherapy; ileocecal syndrome; neutropenia; neutropenic enterocolitis; surgery; typhilite